Chronic hepatitis B virus infection and risk of dyslipidaemia: A cohort study. Issue 1 (29th October 2018) - Joo, Eun‐Jeong; Chang, Yoosoo; Yeom, Joon‐Sup; Cho, Yong Kyun; Ryu, Seungho
Summary: Hepatitis B virus (HBV) infection has been associated with a decreased prevalence of dyslipidaemia in cross‐sectional studies, but cohort studies are limited. We investigated the longitudinal effects of chronic HBV infection on the development of dyslipidaemia. We performed a cohort study of 62 287 non‐cirrhotic adult men and women free of dyslipidaemia who underwent serologic testing for hepatitis B surface antigen (HBsAg) and were followed annually or biennially for an average of 4.46 years. A parametric proportional hazard model was used to estimate the adjusted hazard ratio with 95% confidence interval (CI) for incident dyslipidaemia according to HBsAg seropositivity status. We identified 12 331 incident cases of hypercholesterolaemia during 278 004.4 person‐years of follow‐up (incident rate 44.4 per 1000 person‐years). In models adjusted for age, sex, body mass index, year of screening exam, smoking status, alcohol intake, regular exercise and education level, the adjusted hazard ratios (95% CIs) for incident hypercholesterolaemia, high LDL cholesterolaemia; hypertriglyceridaemia, high non‐HDL cholesterolaemia and low HDL cholesterolaemia comparing HBsAg‐positive to HBsAg‐negative participants was 0.71 (0.64‐0.79), 0.83 (0.78‐0.89), 0.61 (0.54‐0.70), 0.69 (0.63‐0.75) and 1.10 (0.98‐1.24), respectively. An inverse association between HBsAg positivity and incident high apolipoprotein B were also identified, with a corresponding a hazard ratio of 0.63 (0.55‐0.72). In a large cohort of apparently healthy Korean adults, HBsAg seropositivity was associated with lower risk of development of dyslipidaemia, suggesting a role of HBV infection in lipid metabolism.